The military careerist in fourteenth-century England. Issue 1 (1st January 2017) - Ayton, Andrew
ABSTRACT: This article seeks to explain how it was that the careerist soldier became so prominent and ubiquitous a feature of the English military scene during the second half of the fourteenth century. Beginning with a characterisation of the military careerist in his various guises, the discussion proceeds with an investigation of how the pool of militarily employed manpower and the wider recruitment context changed during the fourteenth century owing to the impact of exogenous agencies of change on the dynamics of recruitment. The importance of expanded employment opportunities across Europe and the socio-economic consequences of the Black Death are noted, but particular attention is given to how the English crown's management of war strategy and operations, as well as its influence on army structures and recruitment mechanisms, created a fertile soil within which military careerism could flourish. The roles played by 'supersized' mixed retinues and by opportunities for service in garrisons (especially at Calais) and at sea are considered in turn. The article concludes with an assessment of how the rise of the careerist affected the character of England's military community and the social cohesion of its armies.